HBT Radii: Comparative Studies on Collision Systems and Beam Energies - Debasish Das (Advances in High Energy Physics)
Two-particle Hanbury-Brown-Twiss (HBT) interferometry is an important probe for understanding the space-time structure of particle emission sources in high energy heavy ion collisions. We present the comparative studies of HBT radii in Pb+Pb collisions at sNN = 17.3 GeV with Au+Au collisions at sNN = 19.6 GeV. To further understand this specific energy regime, we also compare the HBT radii for Au+Au collisions at sNN = 19.6 GeV with Cu+Cu collisions at sNN = 22.4 GeV. We have found interesting similarity in the Rout/Rside ratio with mT across the collision systems while comparing the data for this specific energy zone which is interesting as it acts as a bridge from SPS energy regime to the RHIC energy domain.